2012
DOI: 10.1002/chin.201235102
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Regioselective Synthesis and Evaluation of 3‐Alkylidene‐1,3‐dihydroisobenzofurans as Potential Antidepressant Agents.

Abstract: Phthalanes (II) and (IV) are obtained regio‐, stereo‐, and chemoselectively by Cu(II)‐catalyzed cycloisomerization of 2‐ethynylbenzyl alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…26 Zhu and co-workers described the synthesis of 1,3-dihydroisobenzofurans using copper catalysis (Figure 1c). 11 In 2012, Perumal et al reported the synthesis of 1,3-dihydroisobenzofurans and their antidepressant activity (Figure 1d). 11 5-exo-dig cyclization (Figure 1e).…”
Section: ■ Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…26 Zhu and co-workers described the synthesis of 1,3-dihydroisobenzofurans using copper catalysis (Figure 1c). 11 In 2012, Perumal et al reported the synthesis of 1,3-dihydroisobenzofurans and their antidepressant activity (Figure 1d). 11 5-exo-dig cyclization (Figure 1e).…”
Section: ■ Introductionmentioning
confidence: 58%
“…1 Particularly, 1,3-dihydroisobenzofuran (phthalan) derivatives are known to exhibit a wide variety of drug-like properties, 2−5 such as potent antioxidant, 6 antidepressant, antihistaminic, 7 anti-inflammatories, 8,9 and antifungal properties, etc. 10,11 Therefore, the synthesis of dihydroisobenzofurans has drawn considerable attention from the synthetic community. Generally, the intramolecular cyclizations of 2-alkynyl phenyl ketones have been well explored to accomplish isobenzofurans, 12 isocoumarins, 13 isoindoline-1-ones, 14 cyclic imidates, 15 and dihydroisobenzofurans.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation